Criteria for the publication rating of scientific sports journals of the pedagogical industry, reviewed by the higher attestation commission of the Russian Federation - L.I. Lubysheva; V.P. Guba; P.V. Pustoshilo (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify scientometric indicators that increase the publication rating of scientific sports periodicals in the List of journals of the pedagogical industry peer-reviewed by the Higher Attestation Commission of the Russian Federation. Methods and structure of the study. An analysis of information resources, including data on journals reviewed by the Higher Attestation Commission of the Russian Federation (the website of the HAC RF), was carried out. The biblio- and scientometric indicators of periodicals of the scientific electronic platform - eLibrary.ru - have been studied. Results and conclusions. The scientific journals reviewed by the Higher Attestation Commission of the Russian Federation are divided by rating into three categories - K1, K2, K3 - in accordance with the coefficient of scientific significance. Pedagogy in the List of peer-reviewed journals is presented to a lesser extent compared to other scientific areas. To increase the rating and move to the K1 category, it is proposed to turn to the scientometric indicators of the journal "Theory and Practice of Physical Culture", which has been a leader in the field of scientific sports periodicals for many years. In particular, it is recommended to focus on the selection of quality articles, based on indicators of originality, scientific novelty, theoretical and practical significance of the research results.